2020
DOI: 10.3389/fmicb.2020.599739
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Viable but Non-culturable (VBNC) State Formation of Staphylococcus aureus and Its Control in Food System

Abstract: A Viable but non-culturable (VBNC) state is a bacterial survival strategy under reverse conditions. It poses a significant challenge for public health and food safety. In this study, the effect of external environmental conditions including acid, nutrition, and salt concentrations on the formation of S. aureus VBNC states at low temperatures were investigated. Different acidity and nutritional conditions were then applied to food products to control the VBNC state formation. Four different concentration levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 71 publications
0
19
0
Order By: Relevance
“…VBNC was first reported by Xu et al [ 30 ], and this finding was subsequently confirmed by several independent studies, with VBNC now commonly recognized as a critical survival strategy for bacteria [ 31 ]. Furthermore, a number of studies have been carried out globally on VBNC [ 32 , 33 , 34 ], showing the importance of this state on the bacterial life cycle and the implications for the relationship of bacteria with other species, including their hosts. However, there are no reports of VBNC in C. diphtheriae , despite the fact that C. diphtheriae is recognized as a reemerging human pathogen.…”
Section: Discussionmentioning
confidence: 99%
“…VBNC was first reported by Xu et al [ 30 ], and this finding was subsequently confirmed by several independent studies, with VBNC now commonly recognized as a critical survival strategy for bacteria [ 31 ]. Furthermore, a number of studies have been carried out globally on VBNC [ 32 , 33 , 34 ], showing the importance of this state on the bacterial life cycle and the implications for the relationship of bacteria with other species, including their hosts. However, there are no reports of VBNC in C. diphtheriae , despite the fact that C. diphtheriae is recognized as a reemerging human pathogen.…”
Section: Discussionmentioning
confidence: 99%
“…S. epidermidis biofilm-associated infections are often recurrent leading to high rates of morbidity ( Otto, 2009 ). The failure of antibiotics to cure these types of infections is primarily associated with the poor capacity to eradicate biofilms, which are known to have bacterial cells with distinct physiological states ( Rani et al., 2007 ), including viable but non-culturable (VBNC) cells ( Cerca et al., 2011a ; Zhang et al., 2018 ; Li et al., 2020 ). Although VBNC cells cannot grow on standard growth media, these cells present a reduced metabolic activity, replication rate and gene transcription ( Lleo et al., 2000 ; Zhang et al., 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…etc.) can enter quickly to a VBNC state (Afari & Hung, 2018; Duze et al, 2021; Ferro et al, 2018; Lamas et al, 2018; Li et al, 2020). In VBNC stage, the cells usually remain in a state of very low metabolic activity and need special conditions to divide again.…”
Section: Resultsmentioning
confidence: 99%
“…Around 85 species of bacteria have been confirmed as capable of entering into a VBNC state, including 67 pathogenic and 18 non-pathogenic species. (Li et al, 2020). In past studies many of the foodborne pathogens with biofilm forming potential were observed to undergo VBNC state during environmental stresses.…”
Section: Vbnc State Of Foodborne Pathogensmentioning
confidence: 99%